Improve the Quality of Business Decision Making with Accounting Analysis - Cristofer Sumiok; Firayani Firayani; Gilang Ganjar Amrih; Andi Andi (Pt. Anagata Sembagi Education, 2025)
This study aims to examine the role of accounting analysis in improving the quality of business decision-making through the Systematic Literature Review (SLR) approach. This method was chosen to provide a systematic and comprehensive review of previous studies that discuss the relationship between accounting analysis and business decision-making. The literature was collected from various scientific databases such as Google Scholar, Scopus, and ScienceDirect, focusing on publications in the 2020–2025 time frame and using relevant keywords. From the selection results, 15 scientific articles that met the criteria were analyzed thematically. The results of the study show that accounting analysis, through techniques such as financial ratio analysis, cost analysis, and cash flow analysis, makes a significant contribution to the quality of managerial decisions. Decisions based on accounting data have proven to be more rational, measurable, and able to minimize risks, especially in the aspects of financing, investment, and financial planning. In addition, the use of digital technology in the accounting system also strengthens the effectiveness of the analysis by providing information quickly and in real time. However, this study also identifies implementation challenges, especially in the MSME sector, which still faces obstacles such as low accounting literacy and a recording system that has not been digitized. Therefore, improving human resource competency and digitalizing accounting information systems are the main recommendations for optimizing the role of accounting analysis in making quality and sustainable business decisions.